Introduction to nanotechnology: definition, terms, occurrence and applications in environment - MHS Ahmeda; NHS Ahmida; A Ahmeida (Libyan International Medical University Journal)
Nanotechnology is an emerging multidisciplinary technique that involves application based on the synthesis of molecules in nano-scale size range. Nanotechnology is also seen as new and fast emerging field that involves the manufacture, processing and application of structure, device and system by controlling shape and size in nanometer scale. The concept of nanotechnology is driven from the Greek word nano (meaning dwarf). The nano-particles are defined as a discrete entity that has dimensions of the order of 100 nm or less. It is the small size in combination with the chemical composition and surface structure that gives the nano-particles their unique features. The alterations in physical properties serve to enhance versatility and efficacy in product development, resulting in more effective industrial and medical applications. As a result of the widespread use of nanotechnology and nano-materials, these particles find their way into the environment. Therefore, a focus on the source of nano-particles in the environment and their effects is included. This review concentrate on the recent information about analytical developments to assess the occurrence, fate and behavior of nano-materials in environment. It also focuses on the applications of nanotechnology in environment, especially in the area of air and water purifications.